Comparative efficacy of biological and chemical fungicides against Rhizoctonia solani in three rice varieties in Ecuador - Gualberto Isaúl Ramírez-González; Vanessa Elizabeth Pino-Meléndez; Carlos Belezaca-Pinargote; Luis Enrique Sánchez-Jaime; Fernando Javier Cobos-Mora; Germán Reinaldo Troya-Guerrero (Journal of the Selva Andina Biosphere)
The research evaluated the comparative efficacy of biological and chemical fungicides for the control of Rhizoctonia solani Kühn, the causal agent of sheath blight in rice (Oryza sativa L.), using three Peruvian varieties under field conditions in Babahoyo, Ecuador. Twelve treatments were applied with products such as Serenade Max, Timorex Gold, Renaste, Propiconazole and Tebuconazole, plus an absolute control, under a randomised complete block design with factorial arrangement and three replications. Variables evaluated included disease incidence and severity, treatment efficacy, number of tillers, percentage of empty kernels and yield. The results indicated that the treated plots showed lower incidence and severity of R. solani compared to the control, although the efficacy did not exceed 30 %. Variety A3, combined with B1, achieved the highest yield (6749.49 kg ha-¹) and the lowest percentage of empty grains (16.14 %), suggesting a positive interaction between variety and phytosanitary management. It is concluded that the combined use of biological and chemical fungicides, together with adapted varieties, can strengthen integrated phytosanitary management in rice, reducing dependence on synthetic agrochemicals and improving productivity.